VALIDATION OF ECG-BASED, POST-MYOCARDIAL INFARCTION (POST-MI) ESTIMATION OF NON-VIABLE MYOCARDIUM THROUGH TECHNETIUM-99M METHOXYISOBUTYLISONITRILE SINGE PHOTON EMISSION COMPUTED TOMOGRAPHY (TC-99M MIBI SPECT) - Raza, Mehdi; Naz, Zehra; Dar, Zaigham Salim (Pakistan Armed Forces Medical Journal, 2019)
Objective: To validate ECG-based, post-myocardial infarction (post-MI) estimation of non-viable myocardium through Technetium-99m methoxyisobutylisonitrile single photon emission computed tomography (Tc-99m MIBI SPECT).Study Design: Retrospective, diagnostic accuracy study. Place and Duration of Study: Nuclear Cardiology Department, Armed Forces Institute of Cardiology & National Institute of Heart Diseases (AFIC & NIHD), Rawalpindi, from Nov 2018 to Feb 2019.Methodology: This retrospective, diagnostic accuracy study employing consecutive sampling included 142 post-MI patients referred for SPECT myocardial perfusion imaging (MPI). Patients with history of non-ST elevation MI (NSTEMI), bundle branch blocks and unclear/abnormal ECG were excluded. After initial scrutiny, test outcomes data from 105 finally selected patients who underwent the index test (12-lead ECG) and the gold/reference standard (SPECT MPI) were analyzed through 2x2 contingency table.Results: Age and gender distribution in selected patients (n=105) showed an age range of 29 to 90 years (mean age = 58.16 years ± 10.69) and male to female ratio of 6:1 (90 males and 15 females). A 2x2 contingency table was used to compute different 12-lead ECG (index test) parameters. Calculated values were – Sensitivity (Sn) = 56.25%, Specificity (Sp) = 36.58%, Positive predictive value (PPV) = 58.06%, Negative predictive value (NPV) = 34.88% and Accuracy = 48.57%.Conclusion: 12-lead ECG – on validation against SPECT MPI – was found to be a bad test for estimation of non-viable myocardium in post-MI patients.